1998
DOI: 10.1016/s0009-9236(98)90140-0
|View full text |Cite
|
Sign up to set email alerts
|

The substance P receptor antagonist CP-99,994 reduces acute postoperative pain*

Abstract: This replicate demonstration that a NK1 receptor blocker relieves clinical pain supports the hypothesis that substance P contributes to the generation of pain in humans. The reduction in postoperative pain at doses not producing side effects suggests that NK1 antagonists may be clinically useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 43 publications
0
41
1
7
Order By: Relevance
“…The RTX intervention removes the "C-fiber line of communication" but is not equivalent to drugs that block one of the multiple neuroactive substances these neurons release or respond to (e.g., substance P, CGRP, glutamate, bradykinin, prostaglandins). The diversity of transmitters and receptors involved in pain generation suggests that blocking only one element may not yield effective analgesia (6,12,35). In contrast, eliminating the participation of TRPV1-expressing neurons at either the nerve ending or the perikarya reveals the algesic profile of these neurons and their potential as pharmacological targets.…”
Section: Discussionmentioning
confidence: 99%
“…The RTX intervention removes the "C-fiber line of communication" but is not equivalent to drugs that block one of the multiple neuroactive substances these neurons release or respond to (e.g., substance P, CGRP, glutamate, bradykinin, prostaglandins). The diversity of transmitters and receptors involved in pain generation suggests that blocking only one element may not yield effective analgesia (6,12,35). In contrast, eliminating the participation of TRPV1-expressing neurons at either the nerve ending or the perikarya reveals the algesic profile of these neurons and their potential as pharmacological targets.…”
Section: Discussionmentioning
confidence: 99%
“…NK1 receptor antagonists appear able to block behavioral responses to noxious and other stressful sensory pain stimuli at a level detectable in animal tests but fail to provide the level of sensory blockade required to produce clinical analgesia in humans [34]. A variety of reasons have been proposed for the presumed mismatch between the preclinical effects of NK1 receptor antagonists in animal models and their effects in humans including using animal species with different pain pathways to humans and differences in pharmacokinetic parameters [35,36]. Preclinical studies have shown that NK1 receptor antagonists block the neurogenic inflammatory response produced by administration of capsaicin [37,38] and electrical stimulation of the trigeminal ganglion [39].…”
Section: Introductionmentioning
confidence: 99%
“…This disadvantage could be reduced in the compound CP 99.994, which showed a 100fold lower affinity to the L-type Ca 2+ channel in comparison to CP96.345. Although CP 99 994 was tested with some success in preclinical models of nociception and inflammation it could not reveal an advantage compared to ibuprofen in postoperative treatment after dental surgery in humans [214]. GR 205171 (23, Figure 8) (K i 0.4 nM; [215], a trifluoromethyl substituted enantiomer of GR203040 (24, Figure 8) was a further compound with even more reduced nonspecific binding in calcium channels and was in clinical investigations effective to reduce postoperative nausea.…”
Section: Non-peptide Neurokinin Receptor Ligandsmentioning
confidence: 99%